PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL DAN MOTIVASI BELAJAR SISWA MATA PELAJARAN PROSES PEMESINAN DI SMK YPT PRINGSEWU LAMPUNG - Udi Utomo , Wawan (Bappeda Kabupaten Pringsewu, 2016)
Vocational education is a kind of education which develop the talent, basic education of skill, and habit with the aim of working competence which is viewed also as skill training. The objectives of this study are to analyze the differentiations of: 1) the achievement of learning on advanced engineering process subject through the implementation of Project Based Learning (PBL) and Conventional Learning at Vocational High School YPT Pringsewu, Lampung. 2) The motivation of learning on advanced engineering process subject through the implementation of Project Based Learning (PBL) and Conventional Learning at Vocational High School YPT Pringsewu, Lampung. Pre test - pos test control group design was used in this study. The populations of this study were all students of XII engineering major at Vocational High School YPT Pringsewu, Lampung at the academic year 2013/2014 which consisted of 118 students. The random sampling technique was used in this study. The data obtained were analyzed through descriptive statistic and T-Test. The study showed there were on the achievement of learning and motivation of learning on advanced engineering process subject through the implementation of Project Based Learning (PBL) and conventional learning at Vocational High School YPT Pringsewu, Lampung (F= 1.019; with significance level 0.494 bigger than a= 0.05). It means there was no differentiation on the achievement of the students through the implementation of Project Based Learning (PBL) and conventional learning at Vocational High School YPT Pringsewu, Lampung. In descriptive, the mean of the achievement of learning on experimental group was 82.47, while the mean of conventional class was 67.66. The mean of motivation of learning on Project Based Learning class was 80.85; while the mean of conventional class was 69.37